A question of gender? How promotions affect earnings - Aline Zucco; Ann-Christin Bächmann (ZBW - Leibniz Information Centre for Economics, 2020)
Occupational positions can explain an important part of the differences in pay between men and women. However, a considerable Gender Pay Gap exists even within the same occupational position. In this paper, we aim at understanding the reasons for the gap within occupational positions and, therefore, investigate whether promotions lead to the same effect on earnings growth for men and women. Using administrative data, we are the first to investigate potential gender gaps in earnings increase due to a promotion in Germany. Moreover, we are the first to analyze differences in the gender gap across promotions into different occupational positions. Our results emphasize that women's earnings growth are larger than men's after being promoted to the same position. We find that this effect is mainly due to selection since we compare a highly positively selected group of women to an average group of men. Once, we add firm fixed effects, however, gender differences disappear, which highlights the role of collective agreements.
Keywords: J16; M51; J31; J24; 330; Gender; Promotions; Wage Growth